Embodied Irrationality? Knowledge Avoidance, Willful Ignorance, and the Paradox of Autonomy - Arfini, Selene; Magnani, Lorenzo (Frontiers in Psychology, 2021)
In the current philosophical and psychological literature, knowledge avoidance and willful ignorance seem to be almost identical conditions involved in irrational patterns of reasoning. In this paper, we will argue that not only these two phenomena should be distinguished, but that they also fall into different parts of the epistemic rationality-irrationality spectrum. We will adopt an epistemological and embodied perspective to propose a definition for both terms. Then, we will maintain that, while willful ignorance is involved in irrational patterns of reasoning and beliefs, knowledge avoidance should be considered epistemically rational under particular circumstances. We will begin our analysis by considering which of the two phenomena is involved in patterns of reasoning that are still amply recognized as irrational -- as wishful thinking, self-deception, and akrasia. We will then discuss the impact of epistemic feelings -- which are emotional events that depend on epistemic states -- on agents' decision-making. Then, we will consider the impact of willful ignorance and knowledge avoidance on agents' autonomy. By considering these issues, we will argue that when agents are aware that they are avoiding certain information (and aware of what kind of feelings acquiring the information would trigger), knowledge avoidance should be considered a rational, autonomy-increasing, hope-depended selection of information.